Generation and Breakdown of Soluble Ultralarge von Willebrand Factor Multimers - Turner, Nancy; Nolasco, Leticia; Moake, Joel (Seminars in Thrombosis and Hemostasis, 2012)
Ultralarge von Willebrand factor (ULVWF) multimeric strings are rapidly secreted by, and anchored to, stimulated endothelial cells (EC), and are hyperadhesive to platelets until cleavage by ADAMTS-13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13). In ADAMTS-13-deficient familial and autoantibody-mediated thrombotic thrombocytopenic purpura (TTP), there is severely restricted cleavage of EC-anchored ULVWF-platelet strings. The small amount of active enzyme released from their EC cleaves ULVWF strings minimally just above EC surfaces, thus generating soluble ULVWF multimers that are 2.5 to 50 times longer than plasma von Willebrand factor (VWF) forms. Soluble ULVWF multimers (detected in TTP and several other disorders) are also hyperadhesive to platelets and can cause excessive platelet adhesion/aggregation. Without exogenous chemicals or extreme shear stress, soluble ULVWF multimers cannot be cleaved by ADAMTS-13 but can be de-assembled (reduced) in vitro, by a free thiol-containing molecule (>30 kD) present in the cryosupernatant fraction of plasma that is not ADAMTS-13, thrombospondin-1, albumin, cysteine, or glutathione. This reduction may prevent occlusion of the microvasculature by embolic soluble ULVWF multimers (± adherent/aggregated platelets). New inhibitors of platelet adhesion to EC-anchored ULVWF multimeric strings and soluble ULVWF include an aptamer, a nanobody, and N-acetylcysteine.
Keywords: soluble ultralarge von Willebrand factor; ADAMTS-13; reduction; inhibition